DIAGNOSING STUDENTS' MISCONCEPTIONS OF DIRECT CURRENT ELECTRICAL CIRCUITS USING A FIVE-TIER ISOMORPHIC INSTRUMENT - Triani, Elza; Maison, Maison; Nazarudin, Nazarudin (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
This study aims to diagnose students' conceptions and identify their sources related to direct current electrical circuits using a five-tier isomorphic diagnostic instrument. A quantitative method with a research and development design was used involving 108 grade XII students from State Senior High School 1 Jambi City. Data was collected through an isomorphic test of 9 questions, interviews, and documentation. Validity and reliability analysis using SPSS showed that the instrument was reliable (Cronbach's Alpha = 0.911). The implementation of this research instrument showed that the average percentage of students' correct answers (at Tier 1-4) was only 19.9%, indicating a low understanding of the concept. Then, this study also identified students' misconceptions, which included eight main types of misconceptions with an average overall percentage (at Tier 1-4) of 13.6%, which was also categorized as low. Personal thinking was identified as the primary source of misconceptions, providing important insights for designing physics learning interventions. This study's novelty lies in applying a five-tier diagnostic instrument to identify misconceptions and their sources, finding that students' thinking was the primary source. The results of this study provide important implications for physics education, including targeted intervention strategies and increased conceptual clarity, which ultimately support the teaching and learning of basic physics concepts.